Improved electrospray design for aerosol generation and flame propagation analysis. (November 2015) - Lin, Yan-Ru; Chen, Hao; Mashuga, Chad; Mannan, M. Sam
Abstract: Although the hazards of aerosol fires and explosions have been studied for decades the data for aerosol flame propagation is still scarce. Additionally there is a lack of standard techniques and measurement apparatus, which impedes the development of optimal aerosol hazard mitigation measures. The focus of this study is development of an improved aerosol electrospray device for the generation of high quality aerosol data. The goal is achieved through higher nozzle packing, precise nozzle and mesh hole alignment and adding two ground meshes. In addition to a flat ground mesh, the utilization of a cylindrical ground mesh demonstrated improved confinement and guidance of droplets. Duratherm 600, heat transfer fluid, was examined to demonstrate the modified electrospray device capabilities as compared to previous design. Results show the modified electrospray can produce more uniform droplets, more even test chamber dispersion, smaller droplet size and higher concentration aerosol, which is essential to study aerosol flame propagation. Accordingly, the results of aerosol flame speed tests for the improved design were more reproducible. Moreover, it was found that a traditional propane pilot flame was unable to ignite the smaller aerosol droplet size due to the strong turbulence generated by the open flame. However, by careful modification of the pilot flame length, the turbulence decreased dramatically and the small droplet size aerosol can be tested. Highlights: Electrospray was improved to produce high quality aerosol for fundamental study. Ground meshes in different sizes and shapes were verified to give optimal aerosol. Experimental results indicated the flame data were more reliable and reproducible. Different ignition sources were discussed and tested.